Hepatic c-Jun regulates glucose metabolism via FGF21 and modulates body temperature through the neural signals - Fei Xiao; Yajie Guo; Jiali Deng; Feixiang Yuan; Yuzhong Xiao; Lijian Hui; Yu Li; Zhimin Hu; Yuncai Zhou; Kai Li; Xiao Han; Qichen Fang; et al. (Elsevier, 2019)
Objective: c-Jun, a prominent member of the activator protein 1 (AP-1) family, is involved in various physiology processes such as cell death and survival. However, a role of hepatic c-Jun in the whole-body metabolism is poorly understood. Methods: We generated liver-specific c-Jun knock-out (c-jun△li) mice to investigate the effect of hepatic c-Jun on the whole-body physiology, particularly in blood glucose and body temperature. Primary hepatocytes were also used to explore a direct regulation of c-Jun in gluconeogenesis. Results: c-jun△li mice showed higher hepatic gluconeogenic capacity compared with control mice, and similar results were obtained in vitro. In addition, fibroblast growth factor 21 (FGF21) expression was directly inhibited by c-Jun knockdown and adenovirus-mediated hepatic FGF21 over-expression blocked the effect of c-Jun on gluconeogenesis in c-jun△li mice. Interestingly, c-jun△li mice also exhibited higher body temperature, with induced thermogenesis and uncoupling protein 1 (UCP1) expression in brown adipose tissue (BAT). Furthermore, the body temperature became comparable between c-jun△li and control mice at thermoneutral temperature (30 °C). Moreover, the activity of sympathetic nervous system (SNS) was increased in c-jun△li mice and the higher body temperature was inhibited by beta-adrenergic receptor blocker injection. Finally, the activated SNS and increased body temperature in c-jun△li mice was most likely caused by the signals from the brain and hepatic vagus nerve, as the expression of c-Fos (the molecular marker of neuronal activation) was changed in several brain areas controlling body temperature and body temperature was decreased by selective hepatic vagotomy. Conclusions: These data demonstrate a novel function of hepatic c-Jun in the regulation of gluconeogenesis and body temperature via FGF21 and neural signals. Our results also provide novel insights into the organ crosstalk in the regulation of the whole-body physiology. Keywords: Gluconeogenesis, Temperature, Organ crosstalk